Generation Z and Religious Moderation: Building Tolerance in an Era Digital - Anwar, Rosyida Nurul (Journal of Noesantara Islamic Studies, 2025)
Generation Z, which is said to be more open to diversity, must continue to be fostered and improved through revitalizing tolerance values. With easy access to information through digital technology, generation Z has great potential to have an inclusive view of various information, including religious information. Religious moderation is very important in Indonesia, considering that Indonesia is home to various religions and beliefs. This study aims to determine how Generation Z builds tolerance in the digital era. The research method of this study uses qualitative with a phenomenological approach to explore the subjective experiences and understanding of Generation Z regarding religious moderation in the context of the digital era. The location of the study is Universitas PGRI Madiun (UNIPMA), namely students who are Generation Z. Data collection techniques through in-depth interviews and participatory observation. Data analysis techniques using Milles Huberman analysis, namely data reduction, data presentation, and concluding/verification. The study results show that Generation Z is building tolerance in the digital era through a strong understanding of students regarding religious moderation, promoting religious tolerance through digital technology, and participation in online forums. Religious moderation is part of the effort to introduce Islam, which loves peace and compassion.